Rehabilitation of the Nine–banded Armadillo (Dasypus novemcinctus) - McPhee, Suzanne; Leary, Nancy (Wildlife Rehabilitation Bulletin, 2008)
The following is a sampling of substitute formulas, diets, caging facilities, specialized care, and release criteria for the nine–banded armadillo (Dasypus novemcinctus). The information presented should be used as a guideline, not an absolute.